RETELLING RECOUNT STORIES BY USING PICTURE SERIES IN IMPROVING STUDENTS’ SPEAKING SKILL - Afriani, Cici; Apriliaswati, Rahayu; Husin, Syarif (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThe aim of this research was to know how retelling stories by using picture series improved students? speaking skill at the tenth grade students in Class X IPA 1 of SMAN 5 Pontianak in academic year 2017/2018. The research was conducted through Classroom Action Research in three cycles. The subjects of this research were the tenth grade English teacher and 36 students in class X IPA 1. The researcher used observation checklist, field note and speaking performance test as tools to collect the data. The result showed that presenting the materials and modelling retelling stories by using picture series improved students? ability in using appropriate vocabulary, in using correct simple past tense and in using correct pronunciation. Modelling retelling stories by using picture series improved students? ability in reducing pauses and hesitation as they learnt the model to speak fluently. Moreover, presenting the materials, presenting the picture series and modelling retelling stories by using picture series improved students? activeness, students? confidence, students? enthusiasm, and students? interest. In conclusion, retelling recount stories by using picture series improved students? speaking skill.  Keywords: Retelling Stories, Picture Series, Speaking Skill.